2016
DOI: 10.1186/s12864-016-3221-1
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana population analysis reveals high plasticity of the genomic region spanning MSH2, AT3G18530 and AT3G18535 genes and provides evidence for NAHR-driven recurrent CNV events occurring in this location

Abstract: BackgroundIntraspecies copy number variations (CNVs), defined as unbalanced structural variations of specific genomic loci, ≥1 kb in size, are present in the genomes of animals and plants. A growing number of examples indicate that CNVs may have functional significance and contribute to phenotypic diversity. In the model plant Arabidopsis thaliana at least several hundred protein-coding genes might display CNV; however, locus-specific genotyping studies in this plant have not been conducted.ResultsWe analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 66 publications
(76 reference statements)
0
24
0
Order By: Relevance
“…CNVs formed by this mechanism are characterized by tracts of homology on either side of the CNV. NAHR is common in repetitive regions and an important source of tandem duplications and deletions [8]. Another mechanism is single-strand annealing (SSA), which is a doublestrand break repair process where broken ends are joined by annealing at homologies >30 bp in length, which can result in significant deletions [6] ( Figure 1B).…”
Section: Box 1 Cnv Detection Methodsmentioning
confidence: 99%
“…CNVs formed by this mechanism are characterized by tracts of homology on either side of the CNV. NAHR is common in repetitive regions and an important source of tandem duplications and deletions [8]. Another mechanism is single-strand annealing (SSA), which is a doublestrand break repair process where broken ends are joined by annealing at homologies >30 bp in length, which can result in significant deletions [6] ( Figure 1B).…”
Section: Box 1 Cnv Detection Methodsmentioning
confidence: 99%
“…In recent years, whole‐genome sequencing has shown that besides point mutations, copy number variations (CNVs) constitute another important mechanism of genomic variation submitted to selection. This feature has been identified in most model organisms across the plant or animal kingdom (Brown et al., ; Locke et al., ; Yu et al., ; Zmienko, Samelak‐Czajka, Kozlowski, & Figlerowicz, ) and consists of DNA segments typically exceeding 1 kb that are variable in copy number in comparison with a reference genome, share a sequence identity higher than 95% and are dispersed throughout the genome (Alkan, Coe, & Eichler, ). CNVs can either be inherited from the previous generation or appear de novo through duplication/deletion events, and their fixation by drift or selection may contribute to the creation of genetic novelty resulting in species adaptation to stressful or novel environments (Katju & Bergthorsson, ; Kondrashov, ).…”
Section: Introductionmentioning
confidence: 96%
“…However, it is impossible to unequivocally distinguish between real genes and pseudogenes in all cases, because even genes with a premature stop codon or a frameshift mutation could function as a truncated versions or give rise to regulatory RNAs [73, 7678]. In addition, the impact of copy number variations involving protein encoding genes in A. thaliana might be higher than previously assumed thus supporting the existence of multiple gene copies [79]. Gene expression analysis could support the discrimination of pseudogenes, because low gene expression in A. thaliana was reported to be associated with pseudogenization [80].…”
Section: Discussionmentioning
confidence: 99%